Development of a flexible biosensor for the monitoring of lactate in human sweat for its medical use in pressure ischemia - Tur García, Eva (Cranfield University, 2014)
Pressure ischemia is a medical condition characterised by the necrosis of the skin and underlying tissues in body areas exposed to prolonged pressure. This condition leads to the development of bedsores and affects 9% of hospitalised patients, costing the NHS between £1.4 and £2.1 billion per year. The severity of pressure ischemia has been linked to the concentration of sweat lactate, a product of sweat gland metabolism under anaerobic conditions, such as hypoxia. Normal levels of lactate in human sweat are 20±7 mM, but under ischemic conditions these can rise up to approximately 70 mM. This project presents the development of a novel flexible electrochemical enzyme-based biosensor for the continuous and non-invasive monitoring of sweat lactate with the potential for becoming a body-worn device for the early detection of pressure ischemia onset. The core of the recognition system is a flexible laminate, comprising two highly porous polycarbonate membranes, which provide support for the lactate oxidase enzyme, immobilised via covalent cross-linking. Oxidation of lactate produces H2O2, which is subsequently determined electrochemically. The transducer comprises a two-electrode system on a single flexible polycarbonate membrane, sputter-coated with gold (CE/RE) and platinum (WE) to render it conductive. The developed design has been improved through investigation into different factors regarding the immobilisation method of the enzyme in the laminate and the lowering of interferences from oxidising compounds present in sweat. The sensing system exhibits lactate selectivity at physiologically relevant concentrations in sweat for pressure ischemia (0–70 mM), with good reproducibility (7.2–12.2% RSD) for a hand-manufactured device. The reliability of the sensor’s performance and the capability to detect lactate fluctuations on human sweat samples has been demonstrated. The sensing system showed excellent operational and mechanical stability. The application of Nafion® on the WE lowered interferences from ascorbic acid and uric acid by 96.7 and 81.7% respectively. These results show promise towards the further development of a body-‐worn monitoring device for determining lactate levels in undiluted human sweat samples in a reproducible, fast and accurate manner.
Keywords: biosensor; lactate; sweat; pressure ischemia